THE EFFECTIVENESS OF BLENDED LEARNING METHODS AFTER THE COVID-19 PANDEMIC IN THE ENGLISH EDUCATION STUDY PROGRAMME, FACULTY OF EDUCATION, UIKA BOGOR: EFEKTIFITAS METODE PEMBELAJARAN BLENDED LEARNING PASCA PANDEMI COVID-19 DI PRODI PENDIDIKAN BAHASA INGGRIS, FKIP UIKA BOGOR - Wiranata, Afif Ahmad (EDUCATE : Jurnal Teknologi Pendidikan, 2025)
This study aims to find out how effective is the implementation of learning using the blended learning method during the COVID-19 pandemic at the university level, especially UIKA Bogor, Faculty of Teacher Training and Education. This research was conducted using a descriptive qualitative method. The type of this research is survey research. The author uses a mail-questionnaire survey to test respondents' responses by sending questionnaires via social media. In addition, the author also involved the population used for this research, namely students of UIKA Bogor, Faculty of Teacher Training and Education, English Education S1 Study Program, totaling 30 people. The results of this study explain that there are still many students of UIKA Bogor, Faculty of Teacher Training and Education who doubt the effectiveness of learning with the blended learning method. The conclusion in this article is that the blended learning method still needs to be evaluated so that its implementation can run well and as expected.